UNDERSTANDING INTRA-HOUSEHOLD EXPENDITURE DISTRIBUTION IN INDONESIA - Wibowo, Heru (Economic Journal of Emerging Markets, 2014)
Abstract Decentralisation provides regional government with greater authority to deliver various public services. It is expected that decentralisation will improve people welfare due to proximity. This study is aimed to investigate whether there is improvement in welfare, as represented by converging household expenditure, during pre and post decentralisation. It is tested employing Indonesian Family Life Surve (IFLS) database and nonparametric approaches. The findings suggest a converging household expenditure, decreasing gap between the poor and rich, and higher probability of the poor to move to higher expenditure groups, particularly for those who live in urban areas. Keywords: fiscal decentralisation, expenditure convergence, Indonesia JEL Classification number: H77, D31, O53 Abstrak Desentralisasi memberikan pemerintah daerah berbagai kewenangan yang lebih besar untuk memberikan layanan publik. Diharapkan desentralisasi yang akan meningkatkan kesejahteraan masyarakat karena pertimbangan kedekatan. Penelitian ini bertujuan untuk mengetahui apakah terdapat peningkatan kesejahteraan, yang diwakili oleh konvergensi pengeluaran rumah tangga, selama pra dan pasca desentralisasi. Hal ini diuji menggunakan basis data Indonesian Family Life Surve (IFLS) dan pendekatan nonparametrik. Makalah ini menemukan bahwa pengeluaran rumah tangga adalah konvergen, berkurangnya kesenjangan antara probabilitas miskin dan kaya, dan lebih tingginya kemungkinan dari orang miskin untuk berpindah ke kelompok pengeluaran yang lebih tinggi, terutama bagi mereka yang tinggal di daerah perkotaan. Keywords: decentralisasi fiskal, konvergensi belanja, Indonesia JEL Classification number: H77, D31, O53